2012
DOI: 10.1097/igc.0b013e31826a3559
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Cytoreduction in Patients With FIGO Stage IIIC to Stage IV Ovarian, Fallopian, and Peritoneal Cancer in Day-to-Day Practice

Abstract: The findings confirm that complete cytoreduction is the criterion standard of surgery in the management of advanced ovarian, peritoneal, and fallopian tube cancer, whatever the timing of surgery. With experienced teams, surgery was completed, without evident residual tumor in 71% of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 22 publications
9
55
0
1
Order By: Relevance
“…The extent of surgery in patients with advanced ovarian cancer should thus be determined by the performance status and the capacity of the patient to tolerate this very aggressive surgery, as well as by the capacity of a competent surgical team to carry it out with diligence, more than by reason of ages, location, or extent of the illness present at the time of surgery. In spite of the short follow-up time period in these patients, the results obtained are in line with other published studies, and although some results may not be statistically significant, upon comparing complete cytoreduction surgeries with those that were not, a tendency is found towards a gained benefit in terms of intervals free of disease, as has been the case in studies previously cited [22].…”
Section: Discussionsupporting
confidence: 80%
“…The extent of surgery in patients with advanced ovarian cancer should thus be determined by the performance status and the capacity of the patient to tolerate this very aggressive surgery, as well as by the capacity of a competent surgical team to carry it out with diligence, more than by reason of ages, location, or extent of the illness present at the time of surgery. In spite of the short follow-up time period in these patients, the results obtained are in line with other published studies, and although some results may not be statistically significant, upon comparing complete cytoreduction surgeries with those that were not, a tendency is found towards a gained benefit in terms of intervals free of disease, as has been the case in studies previously cited [22].…”
Section: Discussionsupporting
confidence: 80%
“…The prognosis of ovarian cancer is related to cytoreduction, which represents one of the most important treatment factors related to surgery and may even be important in cases of recurrent disease 12,13 . Quality of life, efficacy of subsequent chemotherapy, and median survival each depend on residual tumor volume after cytoreductive surgery 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although previous reports have suggested that neoadjuvant chemotherapy improves the rate of optimal surgical cytoreduction, none have demonstrated that this translates into improved survival. [20][21][22]28,32 In our study, women in the NAC group had a significantly higher rate of optimal cytoreduction than chemothereapy-naive patients undergoing primary cytoreduction. Yet, this did not confer a survival advantage.…”
Section: Discussionmentioning
confidence: 97%
“…[18][19][20][21][22][23][24][25][26][27][28] By contrast, several studies have shown that patients treated with neoadjuvant chemotherapy have a worse survival than those treated with primary surgery. [32][33][34] Overall, controversy remains about the use of neoadjuvant chemotherapy as a first-line treatment strategy for women with newly diagnosed HGSC. Resistant to platinum-based chemotherapy Sensitive -< 0.001* --Cycles of primary chemotherapy > 6 ≤ 6 1.92 (1.43-2.56) < 0.001 --CI = confidence interval, HR = hazard ratio; NAC = neoadjuvant chemotherapy and interval cytoreductive surgery; PCS = primary cytoreductive surgery and adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation